2015
DOI: 10.1007/s10815-015-0570-7
|View full text |Cite
|
Sign up to set email alerts
|

In vitro fertilization in women under 35: counseling should differ by age

Abstract: Purpose The aim of this study is to evaluate the outcomes of in vitro fertilization (IVF), including cumulative live birth rate, among women <25 years, 25 to <30 years, and 30 to <35 years. Methods A retrospective cohort study of all women 18 to <35 years of age at their first fresh-embryo, non-donor IVF cycle from January 1995 through December 2012 at a single center was conducted. A competing-risk regression model was used to estimate the cumulative probability and 95 % confidence interval (CI) of the first … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
5
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 14 publications
(23 reference statements)
1
5
0
Order By: Relevance
“…The clinical pregnancy rate in our study is comparable to published results for the 25- to 35-year age group (35%–36%) [ 24 ]. The clinical pregnancy rate in the thinning group did not differ between age groups (36.7% in those ≤34 years of age vs. 35.1% in those ≥35 years of age).…”
Section: Discussionsupporting
confidence: 90%
“…The clinical pregnancy rate in our study is comparable to published results for the 25- to 35-year age group (35%–36%) [ 24 ]. The clinical pregnancy rate in the thinning group did not differ between age groups (36.7% in those ≤34 years of age vs. 35.1% in those ≥35 years of age).…”
Section: Discussionsupporting
confidence: 90%
“…It is well established that abnormalities in the bidirectional embryo-endometrial dialog are one of the major cause of infertility resulting in implantation failure [2,3]. Noteworthy, advancing maternal age represents one of the major causes of the altered embryo-endometrial communication [4]. As expected, several large studies have reported age-specific outcomes of IVF, and maternal age has clearly been associated with a decline in cumulative live birth rates in patients older than 37 [5,6].…”
Section: Introductionmentioning
confidence: 76%
“…The likelihood of live birth among women age <30 who undergo IVF is excellent. Previous work from this center has shown that after six cycles, 58 % of patients age <25 and 69 % of patients age 25-<30 will achieve a live birth [14]. Why then do women with such positive prognoses for pregnancy discontinue treatment at the same rate as women who have lower chances for success?…”
Section: Discussionmentioning
confidence: 99%